RESPON PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (ALLIUM ASCALONICUM) TERHADAP PEMBERIAN JENIS MULSA DAN PUPUK KANDANG AYAM DI DESA WATUMILOK KECAMATAN KANGAE KABUPATEN SIKKA - Yovita Yasintha Bolly (Agriculture Faculty of Flores University, 2017)
The aim of the study was to find out how the response of onion plants to the administration of mulch and chicken manure was designed using factorial Randomized Block Design (RBD) consisting of 2 factors with 5 treatments and 3 replications. Factor I: The use of Mulch (M) with 3 types, consisting of M0 (without mulch), M1 (rice straw mulch), M2 (Black silver plastic mulch) and Factor II: Chicken manure (P) with 5 levels consisting of P0 ( Without fertilizer), P1 (10 tons / ha or 1 kg / bed), P2 (20 tons / ha or 2 kg / bed), P3 (30 tons / ha or 3 kg / bed) and P4 (40 tons / ha or 4 kg / bed). Observations of age 2 and 6 MST showed that the best treatment was rice straw mulch (M1) where the combination treatment was M1P4 with an average of 34.99 cm in the treatment without mulch (M0) and rice straw mulch (M1). For the number of leaves aged 2 MST showed that the best treatment was rice straw mulch (M1) in the M1P4 combination with a mean of 15.59 strands. Whereas in the second observation the number of leaves aged 6 MST from each treatment was the highest in rice straw mulch (M1) in the M1P4 treatment combined with an average of 46.78 strands. The observation of wet weight on shallots aged 65 HST showed that the combination of mulch and chicken manure on shallots had the first average wet weight in the treatment combination (MOP2) with an average value of 181.48 gr.